Common bean (Phaseolus vulgaris L.) productivity in response to different fertilization strategies - Wellington da Silva Toledo; João Paulo Agápto; Gustavo Fonseca de Almeida (Agro@mbiente On-line)
The feasibility of reducing non-renewable natural resources use in agriculture, associated with the need for ecologically-appropriate of organic waste disposal has become an important element in planning more sustainable agricultural systems. Consequently, the aim of the current study was to evaluate the response of the common bean, growing in an Eutrophic Latosol in the city of Buri-SP, to the application of organic and mineral fertilizers. An experiment was carried out in the 2015 agricultural year, using a randomized block design with 4 replicates and 5 treatments, these being: 1 - mineral fertilizer; 2 - organomineral fertilizer; 3 - sheep manure compost; 4 - chicken bedding compost, and control (soil without fertilizer application). The tested variables were: pod length (cm); per plant pod number; per pod seed number; mass of 100 grains (g); and grain yield (kg ha-1). Organomineral fertilizer provided the most significant increase in pod length, per plant pod number, and yield compared to the other treatments, except for sheep manure compost, where productivity did not differ. In addition, with the exception of mass per 100 seeds, there was no difference between treatments using organic fertilization and mineral fertilizer. Under the current study´s experimental conditions, organomineral fertilizer and sheep manure compost produced the highest productivity for common beans. Thus, mineral fertilization can be replaced by organic or organomineral alternatives, so helping to produce more sustainable production management and help reduce environmental impacts.